The Myths of Creativity - Burkus, David (Ascent Audio, 2020)
There is a mythology around creativity a hazy system of beliefs developed to try to understand what many believe to be incomprehensible. Because of this mythology, many businesspeople view creativity and innovation as vague and inaccessible, assuming that creativity happens through a largely transcendent process of inspiration to which only a select few are granted access. Fortunately for all of us who need to be more creative or lead our organizations through a creativity process, this is simply not the case, and The Myths of Creativity shows how anyone can drop the faulty conventional wisdom of creativity, understand the actual research behind how the creative process works, and ultimately generate impressive creative results. Each chapter of The Myths of Creativity debunks one erroneous assumption about the creative process: Chapter 1: The Sacred Myth: Creativity is not a distant inspiration given to a select few, but comes from within Chapter 2: The Breed Myth: Creativity is not a trait that only certain individuals hold and pass along Chapter 3: The Eureka Myth: Creative insight is not the sudden spark romanticized by stories of Newtons Apple or Archimedes bathtub, but involves a slow hunch Chapter 4: The Originality Myth: Most creative ideas are not unique or original, but are usually new combinations of older ideas. Chapter 5: The Expert Myth: Highly trained experts in a particular domain are sometimes incapable of generating creative insight. Instead, outsiders can provide the fresh perspective needed to creatively solve complex problems. Chapter 6: The Incentive Myth: Traditional incentives like bonuses, awards or other carrots provide little influence on creativity Chapter 7: The Lone Creator Myth: Most innovation is the product of a group of individuals and not any one person. Chapter 8: The Brainstorming Myth: Creativity requires more than merely the rapid generation of ideas. Chapter 9: The Cohesive Myth: Cohesive cultures and feel good environments can hinder innovation. Chapter 10: The Constraints Myth: While the traditional view of creativity is out-of-the-box or no limits, constraints can actually help enhance creativity in individuals and teams. Chapter 11: The Mousetrap Myth: Creative ideas and innovations dont experience immediate celebration like the proverbial better mousetrap. Instead, they often experience backlash as a first reaction. Chapter 12: The Moral Myth: Enhancin...